Low‐Temperature Processed, Efficient, and Highly Reproducible Cesium‐Doped Triple Cation Perovskite Planar Heterojunction Solar Cells. Issue 2 (23rd January 2018) - Wang, Chunhua; Zhang, Chujun; Wang, Shitan; Liu, Gang; Xia, Huayan; Tong, Sichao; He, Jun; Niu, Dongmei; Zhou, Conghua; Ding, Kongxian; Gao, Yongli; Yang, Junliang
Abstract : Highly efficient and reproducible cesium (Cs) doped triple cation (Cs, methylammonium (MA) and formamidinium (FA)) lead trihalide perovskite planar heterojunction (PHJ) solar cells are fabricated via low‐temperature process with a simple architecture of ITO/SnO2 /Perovskite/Spiro‐OMeTAD/Ag, of which the power conversion efficiency (PCE) up to 20.51% with negligible hysteresis and a steady output PCE of 20.22% can be achieved. Cs‐intercalation is useful for forming high‐quality Cs‐doped triple cation perovskite films with larger gains and band gap as compared with perovskite films without Cs doping, leading to impressively enhanced photoluminescence lifetime and open circuit voltage ( V oc ). Meanwhile, incorporating Cs + into perovskite structure can result in lower charge‐extraction time and prolonged charge‐recombination lifetime, which are advantageous to improve the device performance. More importantly, Cs‐doped triple cation PHJ perovskite solar cells (PSCs) exhibit better stability. They could maintain about 80% original PCE even exposed to air environments (humidity ≈40%) for over 500 hr without any encapsulation, while similar ones without Cs‐doping only maintain about 60% original PCE. The research work demonstrates that triple or multiple cation mixture is an effective strategy for structuring highly‐efficient and stable PHJ‐PSCs via low‐temperature process, which may accelerate the commercialization of PSCs fabricated via large‐scale printing techniques. Abstract : Planar heterojunction perovskite solar cells are fabricated via low‐temperature process with an architecture of ITO/SnO2 /Perovskite/Spiro‐OMeTAD/Ag. The power conversion efficiency (PCE) of up to 20.51% with negligible hysteresis and a steady output PCE of 20.22% can be achieved, and ≈80% of the original PCEs can be maintained when exposed to air environment (humidity ≈40%) for over 500 hr without encapsulation.